The Non-Financial Factors Affecting Corporate Social Responsibility Disclosure (CSRD) - Khairunnisa Khairunnisa; Firdaus Abdul Rahman; Rona Naula Oktaviani (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study looks at the relationship of non-disclosure factors to the company corporate social responsibility (CSR). The research focuses on companies that focus on the energy and pulp and paper industries listed on the Indonesia Stock Exchange (IDX). An energy company is a company that uses natural resources as the main raw material in the production of the company's products until they are finally sold to the public. The research was conducted from 2011-2021. Non-financial variables that support the company's CSR activities are corporate governance, independent board, board meeting, risk, and company size. The results of the study show that non-financial factors, namely the independent board, board meetings, company size, and risk have an effect on the company's CSRD. This research cannot be generalized to all companies, because it only focuses on industries engaged in energy and pulp and paper. Future research is expected to use all listed companies and add variables for the company's non-financial factors.